Teori Belajar Behavioristik dan Pandangan Islam Tentang Behavioristik - Fera Andriani (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Abstract: In the view of Islam, the environment is very influential in the formation of a person's development. In which an individual can be conditioned and formed by the surrounding environment. Good environment will form a good personality and vice versa. Then, in the view of Islam, the environment is not an absolute factor for education. Inheritance also carries quite significant influence. Islam considers that the importance of heredity and environment in shaping the development of a person. Nevertheless, the view is more than just that, Islam also views the factors of human endeavor, irodah and Taufiq from Allah SWT in which they play an important role for achieving successful education in the future.